Making do on not much: High energy striving, femininity and friendship in broad city - Kanai, A.; Dobson, Amy (2019)
© 2020 Linkoping University Electronic Press. In the years following the 2008 global financial crisis ("GFC"), feminist media scholarship has drawn attention to the gendered calls in Western media culture to remake subjectivity in line with imperatives of thrift required in conditions of austerity. In the shared symbolic environments that "gender the recession" (Negra & Tasker, 2014), media ranging from news, reality television, and film have placed further, intensified demands on women's domestic, affective, paid and unpaid labour, requiring attitudinal orientations combining future-oriented enthusiasm, positivity, entrepreneurialism, a continued faith in (budget-conscious) consumption and investment in the home and the family. This article considers the US comedy Broad City as an articulation of how young women are critically grappling with such shifts in gendered social relations and labour markets in the cosmopolitan setting of New York City. We suggest, in the depiction of the central female friendship between Abbi Abrams (Abbi Jacobson) and Ilana Wexler (Ilana Glazer) in Broad City, the show foregrounds the necessity of young women's "high energy striving" but produces an alternative configuration of the normative relation between femininity and labour. In the show, contra the "retreatism" Negra and Tasker document idealising women's work in the home as a means of combatting an austere future, the thrifty fun, care, support, and love Abbi and Ilana strive to create together spills across public spaces, spanning the streets of the city, outdoors in parks and on stoops. Abbi and Ilana are continually depicted labouring in some way, though such labour does not generally result in financial or career-based reward, but rather, produces psychic and emotional sustenance for the women's friendship and a means of affectively investing in each other. Thus, in Broad City's acknowledgement of the high energy striving required to survive, the show critically questions the relation of such feminine striving to the promise of career, financial success, and the idealised direction of such striving towards the domestic and hetero-patriarchal family. Instead, the show emphasises the material importance of such striving in relation to the bonds of women's friendship in conditions of material and social hardship, suggesting a different orientation to women's work and its place in recessional culture.